2 - Pour une reprise de la planification économique en Afrique* : by Bruno Bekolo-Ebe - Bruno Bekolo-Ebe (Africa Development, 1993)
With the generalization of adjustment programmes in all African economies, planning as a tool of development has been dropped. The planning exercise is therefore considered as useless and noxious, and is seen as the symbol of state intervention with the numerous constraints imposed to the economy. The withdrawal of the state has brought an end to planning and left adjustment to market forces. After more than fifteen years of implementation of structural adjustment programmes, the result is a complete failure which is characterized by the implementation of various decisions that had a long and negative impact on the future. Long-term vision has been mortgaged. The deepening of the economic crisis and the protracted nature of the desequilibria are now serious enough to recommend going back to planning as an optimal framework for investment choices.